Viruses : Agents of Evolutionary Invention - Cordingley, Michael G. (Harvard University Press, 2017)
While viruses-the world's most abundant biological entities-are not technically alive, they invade, replicate, and evolve within living cells. Michael Cordingley goes beyond our familiarity with infections to show how viruses spur evolutionary change in their hosts and shape global ecosystems, from ocean photosynthesis to drug-resistant bacteria.